2018
DOI: 10.7567/jjap.57.110305
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon assisted improvement of figure of merit of magneto-optical Kerr effect in Au/Co/Au multilayered nanorectangular patch array

Abstract: We observed the significant improvement of the figure of merit (FOM) of the longitudinal magneto-optical Kerr effect in Au/Co/Au multilayered nano rectangular patch array, in which local-mode surface plasmons were resonantly excited by the light irradiation. To demonstrate the advantage of the plasmon excitation, we compared the FOMs in both Au/Co/Au and bare Co nanostructure. Our results clearly show that the incorporation of plasmonic Au structure to magnetic Co layer is effective not only to increase rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…This research field is now called as “magneto-plasmonics 1820 ”. Our group also has reported that the longitudinal magneto-optical Kerr effect and magneto-optical figure of merit in Au/Co/Au nanostructure is enhanced by the localized surface plasmons excitation 21 . According to these reports, the LSPs affect (and modulate) on the magneto-optical property of the magnetic thin film, but it still remains undiscussed whether the surface plasmon excitation affects the magnetization mechanism or not.…”
Section: Introductionmentioning
confidence: 74%
“…This research field is now called as “magneto-plasmonics 1820 ”. Our group also has reported that the longitudinal magneto-optical Kerr effect and magneto-optical figure of merit in Au/Co/Au nanostructure is enhanced by the localized surface plasmons excitation 21 . According to these reports, the LSPs affect (and modulate) on the magneto-optical property of the magnetic thin film, but it still remains undiscussed whether the surface plasmon excitation affects the magnetization mechanism or not.…”
Section: Introductionmentioning
confidence: 74%
“…In other cases, the concept of FoM can be generalized in terms of the readout performance of detection of minimal effects, which is actually strictly related to the signal-to-noise ratio [160]. Related to the latter definition, Kikuchi and Tanaka performed a systematic study on the longitudinal Kerr effect in arrays of Au/Co/Au rectangular meta-atoms, demonstrating that the addition of plasmonic Au layer to the magnetic active Co layer is effective in terms of enhancement of both the optical and magneto-optical responses compared to bare Co nanopatch array [161].…”
Section: Far-field Diffractive Coupling In Magneto-plasmonic Crystalsmentioning
confidence: 99%
“…Recently, advanced studies have been performed on complex Co/Au multilayer structures investigating their hybrid physical properties such as the spin reorientation transition effect [ 32 ], magneto-optic surface plasmon resonance behavior [ 33 , 34 ] and high-order ferromagnetic resonances [ 28 ]. Furthermore, in more application-oriented studies, Co-oxide layers deposited on nanoporous gold substrates have shown highly effective activities for the electrocatalytic reduction of peroxide [ 35 ] and high sensing performance for nonenzymatic glucose [ 36 ].…”
Section: Introductionmentioning
confidence: 99%